2016
DOI: 10.1158/1055-9965.epi-16-0084
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cancer: Associations of Inflammatory Potential of Diet, Cigarette Smoking, and Long-Standing Diabetes

Abstract: Purpose: Non-steroidal anti-inflammatory drugs (NSAIDs) are widely used in the general population, and regular NSAID use is associated with improved survival among colorectal cancer (CRC) patients. We examined the association of NSAID use prior to, and after, diagnosis in relation to CRC-specific and overall survival. Methods: Study subjects were incident, invasive CRC cases from the population-based Seattle Colon Cancer Family Registry. Eligible cases were 20-74 years of age, diagnosed from 1997 to 2008, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…[7][8][9][10][11] Our results are broadly consistent with the published literature, although our estimate for current smoking of 3.4 versus non-smoker is similar to that of a recent study, it is somewhat higher than those previously reported, which range from approximately 1.7 to 2.2. 7,9,10 It is possible that control selection bias contributed to this apparently higher risk.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…[7][8][9][10][11] Our results are broadly consistent with the published literature, although our estimate for current smoking of 3.4 versus non-smoker is similar to that of a recent study, it is somewhat higher than those previously reported, which range from approximately 1.7 to 2.2. 7,9,10 It is possible that control selection bias contributed to this apparently higher risk.…”
Section: Resultssupporting
confidence: 92%
“…Consistent with previous studies, we found that long-term diabetes (≥5 years) was associated with increased risk of pancreatic cancer compared to nondiabetics. 8,12 While short-term diabetes (1-4 years) was associated with nonsignificant higher risk. Unlike other studies that found that patients with short-term (1-4 years) diabetes had a higher pancreatic cancer risk than non-diabetics.…”
Section: Resultsmentioning
confidence: 89%
“…Together, the findings suggest that a pro-inflammatory dietary pattern and genotype-derived non-O blood type are each individually associated with increased PC risk, and that the two exposures do not interact to influence PC risk. Two previous case-control studies conducted at Mayo Clinic (14) and in Italy (15) by our collaborators found that a higher E-DII score was associated with a 2.5-fold increased odds of PC risk. In this study, we replicated those findings in a large, multicenter retrospective case-control sample that included the two prior studies, followed by replication with prospectively collected dietary data from PanScan.…”
Section: Discussionmentioning
confidence: 63%
“…Diet was assessed in each study with validated food frequency questionnaires (FFQ) (14,16,(24)(25)(26)(27)32,(34)(35)(36) or diet history questionnaires (DHQ) (33). All of the dietary instruments used in the participating studies were designed to measure usual dietary habits; however, the periods of diet assessment differed among studies, particularly among the PanC4 studies (Supplementary Tables 5 and 6, available at Carcinogenesis Online).…”
Section: Dietary Assessmentmentioning
confidence: 99%
See 1 more Smart Citation